Ag2MoO4nanoparticles encapsulated in g-C3N4for sunlight photodegradation of pollutants - Wu, M.; Lv, H.; Wang, T.; Ao, Z.; Sun, Hongqi; Wang, C.; An, T.; Wang, Shaobin (Elsevier BV, 2018)
© 2018 Elsevier B.V. Graphitic carbon nitride (g-C 3 N 4 ), a promising metal-free photocatalyst, shows a high thermal stability, excellent chemical stability, and great optical absorption of solar light. However, a short life of activated electron-hole pairs limits g-C 3 N 4 in practical applications. In this work, Ag 2 MoO 4 nanoparticles encapsulated in g-C 3 N 4 (Ag 2 MoO 4 /g-C 3 N 4 ) was synthesized with a facile in-situ precipitation method. A variety of characterization techniques were applied for analyzing the compositions, morphologies and optical properties of Ag 2 MoO 4 /g-C 3 N 4 . The band structure of Ag 2 MoO 4 produces a synergistic effect with g-C 3 N 4 , which can efficiently increase solar light absorption and reduce the recombination rate of the photo-induced electron-hole pairs. Therefore, this hybrid catalyst presents a much higher photocatalytic activity for the degradation of various organic pollutants (bisphenol A, acyclovir, and methyl orange) and strong stability under both artifical and real sunlight, which is promising for practical application.